ANALISIS KEBIJAKAN REALISASI PROGRAM KARTU TANI DI DESA SUDIPAYUNG KECAMATAN NGAMPEL KABUPATEN KENDAL TAHUN 2018 - Lufi Risa Irmayana; Kushandajani . (Journal of Politic and Government Studies, 2019)
The Tani card program is one of the programs of Ganjar Pranowo, the Central Java Governor, Tani Card program is a new program, in Kendal Regency, Tani Cards take effect on January 1, 2018. Tani cards are one of the solutions to overcome the scarcity of subsidized fertilizers and soaring prices of subsidized fertilizers when the fertilization period arrives. After the Tani card, the problem of scarcity of subsidized fertilizers and soaring prices of subsidized fertilizers can be overcome, however, the impact or problems caused by farm cards have not yet been resolved, and until now the Tani card has not been reused and the transaction manually applies again. In this study used the interview method, and related data collection regarding Tani cards. The speakers in this study were is Dinas Pertanian dan Pangan Kabupaten Kendal, Sumberdaya penyuluh pertanian Kecamatan Ngampel Kabupaten Kendal, Ketua Kelompok tani Sudirejeki, Petani Desa Sudipayung, dan pemilik atau penjaga KPL(kios pupuk lengkap). Farmers who have collected the requirements for ownership of Tani cards in Sudipayung village have reached 75%, but in reality there are still many farmers who do not want to take farm cards at Bank BRI as the main partners of Tani Card providers. the awareness of farmers to use Tani cards in Sudipayung village is still very low, this is caused by the existence of a transaction mechanism that is considered by farmers that the majority of the elderly are mostly quite complicated. Tani cards in Sudipayung Village only apply to one planting season, but because of the many problems that cannot be resolved, the Tani card has not been reused until now.